Karakteristik Gender Identity Disorder pada Tokoh Kishimoto Ruka dalam Drama Last Friends Karya Asano Taeko - Adnyana, I Komang Manik (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 2 No 2 (2020), 2020)
The tittle of this research is “Gender Identity Disorder Characteristic at character Kishimoto Ruka in drama Last Friends by Asano Taeko”. This research aims to describe Gender Identity Disorder (GID) characteristic at character Kishimoto Ruka in Last Friends Drama by Asano Taeko. The data were analyzed by using descriptive analysis method and informal method. Some theories applied in this research were Wellek and Warren’s literature and psychology theory (2016), Schmidt’s gender identity disorder theory (1994), Sigmund Freud’s psychoanalytic theory (2016), and Marcel Danesi’s semiotic theory. This research showed that there were four GID characteristics found at character Kishimoto Ruka. These GID characteristic namely 1) there was a sense of cross-gender identification; 2) there was a sense of inappropriateness in the gender role of that sex; 3) the disturbance is not concurrent with a physical intersex condition; and 4) the disturbance causes distress in social and occupational.